Life through the screen: When the meme becomes tradition - Garcia Oltra, Agnés (Eviterna Journal, 2024)
In the immensity of our screen we find a new world, a society without barriers, diverse and in constant evolution, in which the community shares all kinds of images; the interactive coexistence is so broad that it even encompasses different cultures and traditions. For this reason, this article aims to focus on virtual culture through its digital folklore, using elements of this discipline, as well as semiotics, which are argued to be the main methodological tools. Our object of study will be humorous images, specifically the so-called internet memes, and their role as ‘cultural icons’ in contemporary digital folklore. We will analyse their development in the context of web 2.0, with special attention to the case of the Sam Va Lentin meme in Spain. This motif has marked, year after year, the date of 14 February in the national virtual panorama, transforming it into a day where humour, parody, satire and irony take on a leading role. This digital rite, framed within the concept of screenlore, has given rise to novel and original variants, thus establishing itself in the collective memory. Furthermore, the study of internet memes, and in particular the one mentioned above, allows us to better understand the dynamics of digital culture and its impact on society. Through this analysis, we hope to contribute to a deeper understanding of how these types of iconographic resources are integrated and evolve within the coordinates of cyberspace.